Effect of Supplementing Lysine in Distillers Dry Grain with Solubles Based Diets on Weight Gain, Feed Intake and Feed Conversion Ratio in Broiler Chicken - Kumar, Sushil; Sihag, Zile Singh; Sihag, Sajjan; Singh, Narender (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted to determine effect of replacement of soybean meal with distillers dried grains with solubles (DDGS) along with supplementation of lysine on growth performance of broiler chicken. Five hundred and twenty, day-old broiler chicks, were randomly divided into 13 treatment groups each having 4 replicates of 10 birds each. Soybean meal was replaced with DDGS at 0, 15, 30 and 45% DDGS. Lysine was supplemented in DDGS based diets at 0, 0.50, 0.75 and 1% level. Up to 15% replacement of soybean meal with DDGS with or without lysine supplementation had no negative effect on body weight gain, feed intake and FCR at any growth stage. At 30% replacement level, group having 1% lysine supplementation showed similar weight gain and feed intake compared to control group. At 45% replacement level, during initial 2 weeks of age, weight gain was lower (P<0.05) than control group. After initial growth phase, group with 45% DDGS along with 1% lysine showed growth performance similar to that in control group. Groups having lysine supplementation less than 1% had significantly lower body weight gain (P<0.05). During initial growth phase of 2 weeks, groups with 30% DDGS and less than 1% lysine showed higher (P<0.05) body weight gain from the group with 45% DDGS and less than 1% lysine. At 30 and 45% replacement levels, feed intake was higher (P<0.05) when diets were supplemented with less than 1% lysine. FCR at 45% replacement with 1% lysine was similar to that in control.